Accuracy of Image‐Fusion Stereolithographic Guides: Mapping CT Data with Three‐Dimensional Optical Surface Scanning. (17th March 2015) - Widmann, Gerlig; Berggren, Johannes Peter Michael; Fischer, Bastian; Pichler‐Dennhardt, Albina Rosa; Schullian, Peter; Bale, Reto; Puelacher, Wolfgang
Abstract: Background: Computer‐assisted implant surgery usually requires a radiographic scan template as the basis for prosthetic‐driven implant planning and surgical guide fabrication. Purpose: The study aims to evaluate the accuracy of image‐fusion stereolithographic guides in which a computed tomography (CT) scan is mapped with three‐dimensional optical scans of cast and diagnostic wax‐up. Materials and Methods: Three‐dimensional error at the base and tip of the implants, angular deviation of the implant‐axis, and the inserting‐depth error of 120 implants with a length of 10 mm and a caliber of 4.1 mm in 15 polymer‐models were examined. A control CT was performed and fused with the planning data for accuracy evaluation. Results: The mean three‐dimensional error was 0.21 ± 0.10 mm (0.00–0.48 mm) at the implant base, 0.32 ± 0.17 mm (0.03–0.75 mm) at the implant tip, and the mean angular error was 0.85 ± 0.59° (0.00–2.50°). The mean depth error was 0.07 ± 0.07 mm (0.00–0.32 mm). Conclusions: Within the limitations of an in vitro study, the novel technique showed excellent accuracy. Errors from fabrication and scanning of a radiographic scan template can be avoided, and the workflow and costs of computer‐assisted implant surgery may be reduced.